2020
DOI: 10.5435/jaaosglobal-d-20-00120
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Randomized Controlled Trials in Primary Total Hip Arthroplasty (34,020 Patients): What Have We Learnt?

Abstract: Aim: To provide an overview of randomized controlled trials (RCTs) in primary total hip arthroplasty summarizing the available high-quality evidence. Materials and Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PRISMA), we searched the Cochrane Central Register of Controlled Trials (2020, Issue 1), Ovid MEDLINE, and Embase. We excluded nonrandomized trials, trials on neck of femur fractures or revision surgery, systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…No significant differences were observed between the groups at 5 years after THA, for either the primary or secondary outcomes. This is similar to our 2-year results [ 9 ] and to the vast majority of randomized trials in the primary THA population [ 25 ]. We used a rather conservative threshold for clinical relevance for the primary outcome: a difference of 10% [ 7 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…No significant differences were observed between the groups at 5 years after THA, for either the primary or secondary outcomes. This is similar to our 2-year results [ 9 ] and to the vast majority of randomized trials in the primary THA population [ 25 ]. We used a rather conservative threshold for clinical relevance for the primary outcome: a difference of 10% [ 7 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Randomized controlled trials have not consistently shown one technique to be superior to another. 10,11 Some long-term follow-up studies have favoured cementless fixation, 12 and long-term excellent results with cementless stems have been reported, 13 even in elderly patients. 14 International joint arthroplasty registries generally report improved survivorship with cemented stem fixation, 8,15 particularly in elderly patients, while improved survivorship using cementless fixation has been reported in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence available from high-quality RCTs indicates that for the vast majority of patients, a standard conventional THA with a surgical approach familiar to the surgeon, using standard well-established components and XLPE, leads to satisfactory clinical outcomes. 15 …”
Section: Total Hip Arthroplastymentioning
confidence: 99%